Publisher Correction: High-throughput analysis unveils a highly shared satellite DNA library among three species of fish genus Astyanax (Scientific Reports, (2017), 7, 1, (12726), 10.1038/s41598-017-12939-7) - Silva, Duílio M. Z. de A. [UNESP]; Utsunomia, Ricardo [UNESP]; Ruiz-Ruano, Francisco J.; Daniel, Sandro Natal [UNESP]; Porto-Foresti, Fábio [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Oliveira, Claudio [UNESP]; Camacho, Juan Pedro M.; Foresti, Fausto [UNESP] (Springer Nature, 2020)
The original HTML version of this Article contained an error in the Published date ‘5 October 2017’ which was incorrectly given as ‘10 October 2017’. This Article also contained errors in Table 1 where the values in the ‘0B’ and ‘1B’ columns under the ‘Abundance (%)’ section were incorrect by a factor of 100. As a result, in the Results section under the subheading ‘Comparison of satellite distribution in two other Astyanax species’, “However, they were detected bioinformatically in the 0B genome, although at very low abundance (0.00033 and 0.00002%, respectively) (Table 1). now reads: “However, they were detected bioinformatically in the 0B genome, although at very low abundance (0.033 and 0.002%, respectively) (Table 1). Also in the Discussion section, “In fact, we have been able to visualize FISH clusters for ApaSat45-113, which represents only 0.00001% of the 0B genome. now reads: “In fact, we have been able to visualize FISH clusters for ApaSat45-113, which represents only 0.001% of the 0B genome. These errors have now been corrected in the PDF and HTML versions of the Article..